THE PLEA FOR SMALL BUSINESS. - Osborn, Richards C. (The Accounting Review, 1951)
The impression may have been gained that the author feels there are very distinct limits within which small business can be assisted. This is a correct impression. For the majority of small firms there is little that can be done in the way of aid. They provide uneconomic substitutes for jobs which have not been provided elsewhere in American system and the primary solution to the problem is not to be found in perpetuating this state of inefficiency. The continuance of the American economic system is much more dependent on finding an effective way to employ this manpower and these resources than in attempting to continue people in a state of "free" but marginal uncertainty. Most persons are not good entrepreneurs even for a small firm. Certainly there are many fewer good businessmen than the numbers of those who are attempting to be entrepreneurs. Small business is concentrated in the service trades and retailing, fields in which a small amount of capital is required and which involve types of operation that do not compete with the greater efficiency of the mass production industries.